(untitled) (Comillas Journal of International Relations, 2018)
In this article, we examine the most significant changes in the approach and formulation of the two European Union security strategies, presented in 2003 and 2016. This enables us to address fundamental issues related to the evolution of the European Union foreign and security policy since the beginning of the new millennium, in particular analysing the implications for the African continent. On the one hand, the analysis of the central elements of the two strategies allows us to observe a change of direction and a redefinition of the EU’s foreign and security policy, from normative frameworks to newer approaches more focused on the objectives and interests of Europe. On the other hand, we can also observe the evolution of the European Union’s priorities with regard to its approach to the African continent. In this respect, rather than addressing the different areas of mutual interest, the framework for relations between the EU and Africa is dependent on a EU’s limited foreign policy approach, which is preponderantly focused on security issues in Africa.